Experimental study of primary school students’ independent reading based on the network teaching platform - Hui Tang; Min Xu (SHS Web of Conferences, 2023)
The development of information technology, especially the rise of online teaching platforms, has changed the way people read and the methods they use. Under this influence, primary school students’ independent reading has also been changed. However, due to limited self-control and understanding, primary school students face certain difficulties when using online teaching platforms for independent reading. Advantages and disadvantages of distance learning based on the network teaching platform were summarized in this paper. A one-year experiment study was carried out on our school fifth-grade students in independent reading using WeChat campus platform considering their current situation and existing problems of independent reading. In experiment study an independent reading mode was introduced. The results show that this reading mode can significantly improve students’ independent reading ability.